MODERN METHODS OF URBAN ENVIRONMENT LAND USE MONITORING - Pilicheva М.; Kondrashchenko О.; Shterndok Е. (Municipal economy of cities. Series: «Economy science», 2023)
In the context of urbanization and global climate change, the need to adapt and respond to land use dynamics is becoming increasingly important. Cities are constantly transforming, and this transformation affects the social, economic and environmental aspects of the lives of their inhabitants. Accordingly, monitoring tools and methods must be flexible, adaptive and capable of working in real time. Thanks to the latest technologies and monitoring methods, it became possible to quickly analyse changes and predict the future of urban development. In this aspect, remote sensing of the Earth should be noted. The advantages of this tool include: large territorial coverage; high frequency of pictures; the possibility of analysis in different spectral ranges, etc. Geoinformation systems are an equally important tool. GIS allows you to combine, analyse and visualize spatial data. 3D modelling can also be noted as an important tool. With the help of modern technologies, such as laser scanning, it has become possible to create detailed three-dimensional models of urban areas. Separately, automated systems for controlling the use of the territory of cities should be singled out. Due to the proliferation of digital technologies, citizens can actively participate in monitoring processes using mobile applications, public observation platforms and other tools for data collection and sharing. In the monitoring processes of urban land use, mathematical modelling plays a key role in predicting urban land use. The models help researchers and authorities understand current trends and make predictions about the future development of urban areas. Several mathematical modelling approaches can be distinguished, which include: city growth models, geostatistical models, agent-based models, regression models, system dynamic models, optimization models, landscape ecology, diffusion models, socio-economic models, scenario analysis models , combined models. Several different modelling methods are often combined to obtain the most complete and accurate picture.